2022
DOI: 10.1186/s13287-022-02993-y
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific extracellular matrix directs trans-differentiation of mesenchymal stem cells and formation of salivary gland-like organoids in vivo

Abstract: Background Current treatments for salivary gland (SG) hypofunction are palliative and do not address the underlying cause or progression of the disease. SG-derived stem cells have the potential to treat SG hypofunction, but their isolation is challenging, especially when the tissue has been damaged by disease or irradiation for head and neck cancer. In the current study, we test the hypothesis that multipotent bone marrow-derived mesenchymal stem cells (BM-MSCs) in a rat model are capable of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…3 suggest that only cells that formed aggregates during culture with SMG-ECM expressed markers of the SG epithelial cell phenotype. 221
Fig. 3 Ultrastructural characteristics of rat SMG tissue and SMG-ECM-treated aggregates were remarkably similar.
…”
Section: Autologous Multipotent Mscs As a Potential New Therapeutic P...mentioning
confidence: 77%
See 3 more Smart Citations
“…3 suggest that only cells that formed aggregates during culture with SMG-ECM expressed markers of the SG epithelial cell phenotype. 221
Fig. 3 Ultrastructural characteristics of rat SMG tissue and SMG-ECM-treated aggregates were remarkably similar.
…”
Section: Autologous Multipotent Mscs As a Potential New Therapeutic P...mentioning
confidence: 77%
“… 163 More recently, we prepared ECM from decellularized rat SMG tissue, and investigated whether this matrix can direct the trans-differentiation of autologous BM-MSCs to the SG epithelial cell lineage in vitro. 221 We found that culture of BM-MSCs with homogenates of SMG-ECM for 14 days induced the formation of aggregates that expressed SG-specific epithelial cell lineage markers (AQP5, MUC10, KRT14, MIST1) and acinar-associated tight junction proteins (CLDN3 and CLDN10). In addition, the accumulation of glycoprotein/mucin, shown by PAS staining, correlated with the appearance on transmission electron micrographs (TEM) of tight junctions, secretory granule-like structures, and peripheral nuclei, suggesting that the cells were capable of functions associated with differentiated SG cells.…”
Section: Autologous Multipotent Mscs As a Potential New Therapeutic P...mentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, cellular transdifferentiation has been a controversial mechanism by which MSCs improve oral dryness. Previous studies have shown that MSCs can undergo a mesenchymal-to-epithelial transformation when induced by natural SG-specific extracellular matrix and then differentiate into corresponding salivary gland cells to repair damaged glands by replacing damaged salivary gland cells [ 55 ]. Furthermore, when MSCs are co-cultured with SGEC, MSCs can transdifferentiate into SGEC and promote amylase and mucopolysaccharide secretion from salivary gland epithelial cells by inducing salivary gland gene expression [ 45 ], promoting salivary secretion and alleviating oral dryness.…”
Section: Discussionmentioning
confidence: 99%